GeoGebra-Assisted Problem-Based Learning: Enhancing Students’ Mathematical Problem-Solving Ability - Beni Yusepa Ginanjar Putra Putra; Audia Nurul Fitria; Taufik Rahman; Neneng Tita Rosita (MASI Mandiri Edukasi, 2026)
Mathematical problem-solving ability is a crucial competence for students, yet evidence suggests it remains generally low. To address this issue, this study implements GeoGebra-assisted Problem-Based Learning (PBL-GeoG) to enhance students' mathematical problem-solving skills. Using a quantitative approach with a quasi-experimental non-equivalent control group design, the research involved eighth-grade students at a public junior high school in West Bandung Regency during the 2024-2025 academic year. Two classes were selected as samples: class VIII-E as the experimental group receiving the PBL-Geog model and class VIII-C as the control group receiving direct instruction (DI). Data were collected through a validated mathematical problem-solving test and analyzed using IBM SPSS Statistics 23. The results of the independent samples t-test showed a significance value of 0.000 ( < 0.05). The findings conclude that the improvement in mathematical problem-solving skills among students taught with the GeoGebra-assisted Problem-Based Learning model is significantly higher than that of students taught through direct instruction.